Instrumental Composition Methods of Oud Players in Iraq (Al-Academy, 2026)
Many oud players from generations after the early students of Sharif Muhyiddin Haidar have created diverse melodies in various instrumental musical forms and styles, creating new and different spaces for expression. This raises questions about the manner, method, style, or genre to which these players belong, and this research is concerned with studying this topic.The importance of the research lies in its focus on studying methods of Arabic musical composition and its support for the development of composition and musical writing for the oud and other instruments. The research dealt within its theoretical framework with three topics, in order: (the concept of musical composition and composing), (characteristics of Arabic instrumental music), and (the oud in contemporary Iraqi music).This research also studied samples chosen intentionally, representing the community of Iraqi oud players, which was determined to be (22 players). After analysis using a criterion designed for this purpose, the research reached a set of results and conclusions, the most important of which is that the majority of oud players in Iraq possess talents in composing and innovating music according to Arab instrumental composition, which deals with specific musical elements, namely melody, rhythm, form, and performance, and not according to the rules, systems, and controls of international composition that deal with all musical elements, as their methods adhered to and did not deviate from what is common in Iraqi and Arab music and singing